2023
DOI: 10.3390/ijms24087462
|View full text |Cite
|
Sign up to set email alerts
|

Blood Platelets in Infection: The Multiple Roles of the Platelet Signalling Machinery

Abstract: Platelets are classically recognized for their important role in hemostasis and thrombosis but they are also involved in many other physiological and pathophysiological processes, including infection. Platelets are among the first cells recruited to sites of inflammation and infection and they exert their antimicrobial response actively cooperating with the immune system. This review aims to summarize the current knowledge on platelet receptor interaction with different types of pathogens and the consequent mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 152 publications
0
8
0
Order By: Relevance
“…TF and Factor VIIa combine to aid in the formation of the prothrombinase complex on the exterior of triggered platelets, thereby producing high quantities of thrombin. Interestingly, researchers [ 3 , 9 ] have shown that platelet-specific P-selectin deficiency alters the initiation of atherosclerosis in a preclinical model of atherosclerosis based on the work of Russell Ross [ 1 ]. This modification has the potential to decrease smooth muscle cell mobility, which may significantly impact lipid levels and the number of cells in the growing plaque [ 36 , 37 , 38 , 39 ].…”
Section: Understanding the Role Of Platelets And P-selectin As Key Ac...mentioning
confidence: 99%
See 2 more Smart Citations
“…TF and Factor VIIa combine to aid in the formation of the prothrombinase complex on the exterior of triggered platelets, thereby producing high quantities of thrombin. Interestingly, researchers [ 3 , 9 ] have shown that platelet-specific P-selectin deficiency alters the initiation of atherosclerosis in a preclinical model of atherosclerosis based on the work of Russell Ross [ 1 ]. This modification has the potential to decrease smooth muscle cell mobility, which may significantly impact lipid levels and the number of cells in the growing plaque [ 36 , 37 , 38 , 39 ].…”
Section: Understanding the Role Of Platelets And P-selectin As Key Ac...mentioning
confidence: 99%
“…Recent studies show that deep vein thrombosis formation is not only related to platelets and red blood cells, but also involves monocytes and neutrophils [ 168 , 169 , 170 ]. Researchers have been aware of the role of platelets and platelet-derived factors in inflammation since the beginning with ongoing research supporting their impact [ 2 , 3 , 7 , 32 , 102 ]. The traditional cellular players of inflammation and thrombosis fully intertwine, validating the term thromboinflammation.…”
Section: Nex Stepsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of CDI, severe infection could lead to sepsis and extra-intestinal infection (Lowenkron et al, 1996;Libby and Bearman, 2009;Steele et al, 2012;Abid and Bischof, 2019;Olsen et al, 2023). Moreover, inflammation in the gut can induce platelet activation and migration (Gaertner et al, 2017;Shannon, 2021;Trivigno et al, 2023), then platelets attached to the activated endothelium promote monocyte migration (Huilcaman et al, 2022;Trivigno et al, 2023). Beneficial or detrimental roles related to clinical symptoms have been reported for platelets counts during CDI (Pant et al, 2009;Byrn et al, 2012;Lee et al, 2014;Yan et al, 2017;Mihaȋlăet al, 2019;Nseir et al, 2019;Allegretti et al, 2020;Phanchana et al, 2020;Zhao et al, 2020;Buchrits et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…1 As a booster of cancer, platelets participate in various physiological and pathological processes, such as hemostasis, metastasis, wound healing, angiogenesis, inflammation, and thrombosis. 2,3 Extensive research has validated that the intravascular platelets in tumor tissues can secrete multiple angiogenic regulatory factors to facilitate the formation and distribution of blood vessels in tumors. 4 When escaping from vessels, platelets will gather in tumor tissues and directly contact tumor cells or secrete transforming growth factor-β, hepatocyte growth factor, and platelet-derived factor to promote the epithelial–mesenchymal transformation (EMT).…”
Section: Introductionmentioning
confidence: 99%